The potential of lake in generating the urban community development, case study : Putrajaya Lake, Federal of Putrajaya / Wan Noor Anira Hj Wan Ali @ Yaacob ... [et al.] - Wan Noor Anira, Wan Ali @ Yaacob; Norhafizah, Abdul Rahman; Marina, Abdullah; Nor Izana, Mohd Shobri (2015)
Lake is not only the recreational area for people but also promote physical and economic development. Lake in urban environments is an important sources to remote and protects our natural environments. Lake also gives benefit to create positive social, culture and physical development in urban community. In Canada, the Ontario Lake is an axial development of their commercial, residential, tourism and also as recreational areas. However, in Malaysia lake development is still diffident and less comprehensive as a community centre in socio- culture environment. Therefore, the purpose of this study is to interconnect the design implementation and the potential of Putrajaya Lake with the Putrajaya community and the land use (commercial, residential, recreational and administration) areas. The research methodology is based on site inventory, site analysis and also using primary and secondary data. The findings were used in helping Putrajaya Lake expand its sense of ownership among their community as well as in constructing Putrajaya Lake as an enormous destination of water recreation. Furthermore, Putrajaya Lake is known to have an acceptable urban setting condition with higher quality water level to cater its multi-functional uses such as for boating, fishing, recreational and water sport. This will help Putrajaya to achieve its inspiration of “City in a Garden”.